Tantangan dan Strategi dalam Penyusunan Laporan Keuangan Berkualitas dengan SIPD: Studi Kualitatif di Kabupaten Tojo Una-Una - Naida, Nasrun; Sartika, Dewi (Kajian Ekonomi dan Bisnis, 2024)
This study examines the modernization of regional financial management to enhance transparency, accountability, and efficiency in Tojo Una-Una Regency. By implementing the Regional Government Information System (SIPD) with the Accounting and Reporting (AKLAP) module since 2022, the Regional Financial and Asset Management Agency (BPKAD) aims to improve the quality of financial reports in accordance with government accounting standards. However, limitations in human resource (HR) competence and a lack of technical training for operators hinder optimal integration and report accuracy. Using a descriptive qualitative method with an inductive approach, this research identifies barriers and SIPD optimization strategies through interviews and observations. Key findings indicate that limited HR competence and unequal technological infrastructure across Regional Government Organizations (OPD) are the main obstacles. Recommendations include intensive training for SIPD operators and strengthening technology infrastructure at the OPD level, which are expected to enhance regional financial management performance, creating a more transparent, accurate, and accountable system